Evaluation of survival and ischaemic and thromboembolic event rates in patients with non-valvar atrial fibrillation in the general population when treated and untreated with warfarin. Issue 2 (9th May 2005) - Currie, C J; Jones, M; Goodfellow, J; McEwan, P; Morgan, C L; Emmas, C; Peters, J R
Abstract : Objective: To compare survival and adverse outcome of patients with non-valvar atrial fibrillation (NVAF) treated with or without warfarin. Design: Record linkage method to identify patients with a previous hospital diagnosis of atrial fibrillation and to link these patients to international normalised ratio (INR) test results and mortality data. Setting: Cardiff and the Vale of Glamorgan, Wales. Main outcome measures: Mortality, specifically from ischaemic and thromboembolic events. Results: 6108 patients were identified with NVAF, of whom 36.4% received warfarin. Mean survival in the warfarin and non-warfarin groups was 52.0 months and 38.2 months, respectively (p < 0.001), and 14.4 months (p < 0.001) after adjustment for confounding factors. Warfarin treated patients in the upper quartile of INR control had significantly longer survival (57.5 months) than did those in the lowest quartile of control (38.1 months, p < 0.001). The risk of stroke in the warfarin group when treated was lower than that in the non-warfarin group (relative rate (RR) 0.74, p < 0.001). The risk of death from ischaemic stroke was lower in the warfarin group (RR 0.43, p < 0.001). The risk of all ischaemic and embolic events in the warfarin group was lower when they were taking warfarin (RR 0.74, p < 0.001). The risk of bleeding in the warfarin group when treated was greater (RR 1.78, p  =  0.001). Conclusions: Patients with NVAF within the recommended target INR range of 2.0–3.0 survive longer and have reduced morbidity. Probably too few people are anticoagulated with warfarin in NVAF.